2017
DOI: 10.21873/anticanres.11334
|View full text |Cite
|
Sign up to set email alerts
|

Possible Therapeutic Effects of Ozone Mixture on Hypoxia in Tumor Development

Abstract: Recent literature highlights that ozone therapy could be considered a viable adjuvant therapy in oncological patients receiving radio-chemotherapy. The use of ozone therapy in these patients enhances the action of chemotherapy and at the same time reduces side-effects, such as nausea, vomiting, opportunistic infections, buccal ulcers, hair loss and fatigue. Such positive therapeutic effects of ozone therapy can cause a larger physical and mental wellbeing resulting in improved quality of life. This work review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 72 publications
0
19
0
6
Order By: Relevance
“…mucosa. Ozone therapy utilizes ozone to increase the amount of oxygen in the blood and is used for treating cancer and other diseases (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…mucosa. Ozone therapy utilizes ozone to increase the amount of oxygen in the blood and is used for treating cancer and other diseases (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Despite not being observed in all cases, in tumors in which O 3 T does increase tumor oxygenation, the effects of RT and CT could be enhanced, especially if this oxygenation increase is produced in zones of tumor hypoxia, i.e., in those that are most radio-resistant. Reviews, by Bocci et al in 2005 [ 54 ] and, more recently, by Luongo et al in 2017 [ 55 ], addressed the potential molecular and cellular pathways related to the effects of ozone on tumor hypoxia, tumor microenvironment, and tumor development [ 54 , 55 ]. Their hypotheses are further supported by an experimental study of diabetic nephropathy in rats, which reported that ozone diminishes the previously elevated expression of hypoxia-inducible factor-1 α (HIF-1 α ) [ 56 ].…”
Section: Tumor Hypoxia/ischemia Modification As a Potential Methodmentioning
confidence: 99%
“…Применительно к заявленным целям адъювантного лечения -элиминации злокачественно трансформированных клеток, обнаруженные эффекты ставят под сомнение целесообразность включения озонотерапии в комплексное консервативное лечение онкологических больных [15].…”
Section: оригинальные статьиunclassified